Gayatri Rajapatni : perempuan di balik kejayaan Majapahit - Drake, Earl.; Budiman, Manneke, 1965- (Yogyakarta : Ombak, 2012)
Role of Gayatri Rajapatni, the consort of Krtarejasa Jayawardhana, founder of Majapahit, in the history of Majapahit Kingdom.
Includes bibliographical references (p. 184-187) and index.
Keywords: Gayatri Rajapatni, -- consort of Krtarajasa Jayawardhana, King of Majapahit, -- 1274-1350.; Majapahit (Kingdom) -- History